SELECTING VEGETATION INDEX FOR MAPPING LAND USE AND COVER CHANGE (2019-2021) TOWARD SUSTAINABLE MANAGEMENT IN XAYTHANY DISTRICT, VIENTIANE LAO PDR - MAOKHAMPHIOU, Touksamphanh; Duy Quang, Pham; Hai Hoa, Nguyen; Van Truong, Vu; Phu Tuan, Le (Journal of Forestry Science and Technology, 2022)
Remote sensing technology offers an effective tool to monitor the changes in land use/cover over time. This study tested five vegetation indices for land-use/cover mapping and SAVI was then selected with thresholds defined for land cover (SAVI > 0.52 for forest cover; SAVI > 0.21 and SAVI <= 0.52 for agriculture; SAVI > 0.05 and SAVI <= 0.21 for others; SAVI <=0.05 for water). The overall accuracy assessments of land use/cover in 2019 (91.0% of accuracy, Kappa coefficient of 0.87), in 2020 (93.0% of accuracy, Kappa coefficient of 0.90), and in 2021 (94.5% of accuracy, Kappa coefficient of 0.92) have confirmed using Sentinel-2 data for monitoring the spatio-temporal changes of land-use/cover is reliable in Xaythany District. The extent of ​​forest cover in Xaythany District, Vientiane Province in 2019 and 2021 were 31659.1 ha and 31369.9 ha, the area of ​​agriculture in 2019 and 2021 were estimated at 40511.3 ha and 41105.9 ha, respectively. In addition, forest cover in Xaythany District decreased by 289.2 ha in 2021 compared to 2019 and main drivers for deforestation and land use/cover change during the period of 2019-2021 were defined in the order of slash-burning and shifting cultivation, other land use conversions, and other socioeconomic influences.